(untitled) - Powers, Chase (New York, 1999)
The book gives every aspect of efficiently heating homes - weather it's selecting the right equipment and keeping it running smoothly, or tackling commonly encoutered problems with heat pumps and boilers.
Keywords: Heating; Handbooks, manuals, etc